Upper and Lower Solution Method for Fractional Boundary Value Problems on the Half-Line - Dandan Yang; Chuanzhi Bai (Journal of Applied Mathematics)
We establish the existence of unbounded solutions for nonlinear fractional boundary value problems on the half-line. By the upper and lower solution method technique, sufficient conditions for the existence of solutions for the fractional boundary value problems are established. An example is presented to illustrate our main result.